Estimated Manipulation of Tablets and Capsules to Meet Dose Requirements for Chinese Children: A Cross-Sectional Study - Zhang, Liwen; Hu, Yan; Pan, Panpan; Hong, Chengtao; Fang, Luo (Frontiers in Pediatrics, 2021)
Objectives: To estimate the frequency of manipulations of all tablets and capsules prescribed for children in a teaching and tertiary children’s hospital in China over the course of 1 month. Moreover, hypothetical reduction of manipulation according to the availability of low-strength tablets/capsules licensed by the Chinese National Medical Products Administration (CNMPA) was evaluated. Methods: Information on all tablets and capsules prescribed in the hospital from March 17 to April 16, 2019 was collected. It was assumed that tablets or capsules were manipulated if the prescribed dose would have required only a proportion of the intact dose form. Manipulation typically includes splitting or crushing tablets, opening capsules and dispersing in water, or combinations of these method. Moreover, we defined an “avoidable manipulation”, when the dose could be rounded and/or when alternative products with a reduced strength or in liquid formulation were available in the hospital, and a “inappropriate manipulation”, which involved manipulated medications with a direct contraindication for any manipulation, such as those with a narrow therapeutic index or hazardous ingredients, or modified release dosage-forms. The frequencies of total, avoidable, and inappropriate manipulation were estimated, along with the hypothetical reduction of manipulation according to the availability of CNMPA-approved drug doses. Results: A total of 17,123 prescriptions for 142 medications were identified to have required a manipulation among 78,366 prescriptions administered during the study period, with 43 different proportions of subdivisions, ranging from a 19/20 to 1/180 product strength reduction. Half, quarter, and trisection were the most common subdivisions administered. Overall, 19% of the manipulated prescriptions were determined to be avoidable, and 19% of the manipulations involved medications with a clear recommendation to not manipulate. In addition, 21% of the manipulated prescriptions could have been potentially avoided if all of the approved preparations with the lowest strength would have been available at the hospital. Any manipulations undertaken were carried out by pharmacists and family care givers. Conclusions: More than 20% of tablets and capsules prescriptions need manipulated, included a high incidence of avoidable and inappropriate manipulation.